Adult attention-deficit/hyperactivity disorder and its association with substance use and substance use disorders in young men. (20th May 2015) - Estévez, N.; Dey, M.; Eich-Höchli, D.; Foster, S.; Gmel, G.; Mohler-Kuo, M.
Abstract : Background: Functional and mental health impairments that adults with attention-deficit/hyperactivity disorder (ADHD) experience may be exacerbated by regular substance use and co-morbidity with substance use disorders (SUD). This may be especially true during young adulthood, which represents a critical stage of life associated with increased substance use and associated problems. However, previous studies investigating the association between ADHD and substance use and SUD have demonstrated inconsistent results, probably due to methodological limitations (e.g., small and non-representative samples). Thus, the relationship of ADHD with substance use and related disorders remains unclear. The aim of the present study was to examine the association between ADHD and both the use of licit and illicit substances and the presence of SUD in a large, representative sample of young men. Method: The sample included 5677 Swiss men (mean age 20 ± 1.23 years) who participated in the Cohort Study on Substance Use Risk Factors (C-SURF). ADHD was assessed using the adult ADHD Self Report Screener (ASRS). The association between ADHD and substance use and SUD was assessed for alcohol, nicotine, cannabis and other illicit drugs, while controlling for socio-demographic variables and co-morbid psychiatric disorders (i.e., major depression (MD) and anti-social personality disorder (ASPD)). Results: Men with ADHD were more likely to report having used nicotine, cannabis and other illicit drugs at some time in their life, but not alcohol. ADHD was positively associated with early initiation of alcohol, nicotine and cannabis use, the risky use of these substances, and the presence of alcohol use disorders, and nicotine and cannabis dependence. Additionally, our analyses revealed that these patterns are also highly associated with ASPD. After adjusting for this disorder, the association between ADHD and licit and illicit substance use and the presence of SUDs was reduced, but remained significant. Conclusions: Our findings suggest that adult ADHD is significantly associated with a propensity to experiment with licit and illicit substances, especially at earlier ages, to exhibit risky substance use patterns, and to subsequently develop SUDs. Preventive strategies that include early intervention and addressing co-morbidity with ASPD may be crucial to reducing substance use and the development of pathological substance use patterns in young men affected by ADHD and, thus, helping to prevent further illness burden later in life.